Imaging switchable magnetoelectric quadrupole domains via nonreciprocal linear dichroism - Kenta Kimura; Tsukasa Katsuyoshi; Yuya Sawada; Shojiro Kimura; Tsuyoshi Kimura (Communications Materials, 2020)
Magnetoelectric multipoles are parity and time-reversal odd structures emerging in multiferroic and exotic ordered phases. Here, the discovery of nonreciprocal linear dichroism in Pb(TiO)Cu4(PO4)4 enables a fast visualization of magnetic quadrupole domains using simple linear polarization microscopy.